2022
DOI: 10.1515/biol-2022-0057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical-based fertilizer replacement with biochar-based fertilizer on albic soil nutrient content and maize yield

Abstract: Biochar-based fertilizers are used to improve soil’s physiochemical and biological properties and increase fertilizer utilization rate. Therefore, a technological model of biochar-based fertilizers is essential for the reduced application. This study was conducted to determine the effects of the different levels of biochar-based fertilizer applications on soil and plant nutrient content, as well as maize yield. Biochar-based fertilizer increased the total N content of maize stem and kernel and the total P cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Biochar effect is soil type-dependent; for example, for decreasing sandy soil bulk density, at least 1% of biochar addition is required, whereas it was at least 5% for sand-loam soil [12,13]. Indeed, it is frequently reported that the application of biochar to soil for ameliorating its properties and enhancing crop productivity is more successful with well-weathered soils (degraded), low fertility soils, and acidic soils, than with fertile healthy soils [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar effect is soil type-dependent; for example, for decreasing sandy soil bulk density, at least 1% of biochar addition is required, whereas it was at least 5% for sand-loam soil [12,13]. Indeed, it is frequently reported that the application of biochar to soil for ameliorating its properties and enhancing crop productivity is more successful with well-weathered soils (degraded), low fertility soils, and acidic soils, than with fertile healthy soils [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, biochar addition possibly stimulated and enhanced effects of the fertilizer. It is reported in previous studies that due to the rich porous structure of biochar, it can effectively absorb and store nutrients in fertilizer (with high nutrient retention capacity), reducing nutrient loss and prolonging fertilizer effects [24]. On the other hand, due to its huge specific surface area, biochar can also improve soil structure and provide growth space for soil microorganisms, promote microbial activity, contribute to the decomposition and transformation of organic fertilizer, and release more nutrients for crops to absorb [25].…”
Section: Growth and Yieldmentioning
confidence: 99%
“…The carbon content increases as other elements are removed from the biomass through thermochemical conversion. Biochar is a high-value product that has been used to reduce greenhouse gas emissions, improve soil nutrients, and prepare energy storage devices [ 25 , 26 , 27 ]. Singh et al [ 28 ] utilized biochar and plastic char derived from biomass materials and waste plastics, respectively, to eliminate heavy metals from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%